Critical appraisal on Bacterial Concrete - Saifee, Sakina Najmuddin; Lad, Divya Maheshbhai; Juremalani, Jayesh Rameshbhai (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
It is an unique technique in which the bacteria undergo bio- chemical process inside the concrete in presence of calcite mineral and leads to the formation of precipitates which helps in sealing of pores and cracks generated inside the concrete. This technique is studied now a days and research is being done on use of different bacteria as sustainable and concrete embedded self-healing agent. Various materials used for repair available in market like polymers epoxies etc… are harmful to the environment; Hence this technique being environmental friendly can be used as their substitute. It was also observed in the study that the metabolic activities in the microorganisms taking place inside the concrete results into increasing the overall performance of concrete including its compressive strength. Thus, this paper is an attempt to define bacterial concrete, types ,classification of bacteria, process of fixing the cracks using these bacteria’s , application and advantages as well as dis advantages of bacterial concrete in the field of construction by literature view are discussed.